Lucid dreaming: effects of culture in a US American sample - Schredl, Michael; Bulkeley, Kelly (Dreaming, 2020)
Lucid dreaming is defined as a dream in which an individual becomes consciously aware that s/he is dreaming while dreaming. Concepts about lucid dreaming vary strongly in different cultures. The present survey was completed by 3,992 Americans 18 years and older in age (2,310 women and 1,682 men), with a mean age of 48.26 +/- 17.09 years. Lucid dream occurrence in the total sample was 35.72%, with Hispanic participants reporting a significantly lower frequency of lucid dreams compared with White participants, a difference that might reflect a greater prominence of lucid dreaming in more individualistic cultures versus more communitarian cultures. Although the findings of this study suggest specific cultural effects on lucid dream frequency and other aspects of dreaming, more empirical research is needed to help to clarify how strongly these effects may appear in dreaming in general, and lucid dreaming in particular, among a wider range of today's world population.